Polyphenylene sulfide resin and preparation method thereof
During the polyphenylene sulfide polymerization process, when the conversion rate of the dihalogen aromatic compound is greater than 50%, the material is in a turbulent state, which solves the problem of high generation of oligomer ultrafine powder waste, and improves polymerization yield and excellent yellowing resistance.
Patent Information
- Application Number
- CN202411914996.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
AI Technical Summary
The high amount of oligomer ultra-fine powder waste generated during the polyphenylene sulfide polymerization process, resulting in increased environmental pollution and production costs, affecting economic benefits.
When the conversion rate of dihalogen aromatic compounds is greater than 50%, the material is placed in a turbulent state through the external circulation pipeline, strengthening the mixing effect of the polymerization system, and reducing the generation of oligomer ultra-fine powder waste.
The amount of oligomer ultrafine powder waste is significantly reduced, the polymerization yield is improved, and the polyphenylene sulfide resin has excellent yellowing resistance.
Smart Images

Figure FT_1 
Figure BDA0005206626570000021 
Figure BDA0005206626570000061
Abstract
Description
Technical Field
[0001] The invention relates to a polyphenylene sulfide resin and a preparation method thereof, belonging to the technical field of polymer materials. Background Art
[0002] Polyphenylene sulfide (PPS for short), as an emerging high-performance thermoplastic resin material, occupies an important position in the field of materials science due to its excellent high temperature resistance, corrosion resistance, balanced mechanical properties and outstanding dimensional stability. It is known as the world's sixth largest engineering plastic and is widely used in many fields such as the automotive industry, electronic appliances and environmental protection industry.
[0003] Phillips Petroleum Company prepared PPS through the polymerization reaction of p-dichlorobenzene (p-DCB) and sodium sulfide in polar aprotic solvents, and took the lead in realizing the industrialization and commercial production of PPS. However, the first generation of PPS products faced the challenges of low molecular weight and low melt viscosity, and further cross-linking and curing were required to increase its molecular weight to meet application requirements.
[0004] In order to improve the quality of PPS products, subsequent research focuses on improving the polymerization process, such as adding polymerization aids such as water (JP1988039926A), alkali metal halides (JP2007106784A), alkali metal carboxylates (US5342654A) and alkaline earth metal aromatic carboxylic acids (JP1989043169) to promote the formation of high molecular weight PPS. Although the strategy of adding polymerization aids can achieve the increase of PPS molecular weight, its effect on improving polymerization yield is relatively limited; a large amount of ultrafine powder waste of PPS oligomers will inevitably be produced during the polymerization process. The ultrafine powder waste of oligomers has the characteristics of complex composition, difficulty in further polymerization and extremely small particle size, which together constitute a challenge in treatment. At present, most of this waste is classified as solid waste for treatment. This situation not only increases the environmental burden, but also the harmless treatment measures adopted also increase the production cost and complicate the production process, which has an adverse impact on the economic benefits of polyphenylene sulfide industrial production.
[0005] Many patented technologies are dedicated to improving polymerization yield and reducing the generation of ultrafine powder waste of oligomers. For example, CN107075117 introduces a method of introducing a multifunctional compound when the conversion rate of dihalogen aromatic compounds exceeds 50% to promote the repolymerization of some oligomers, and finally makes the generation of ultrafine powder waste of oligomers less than 6%. However, the method of introducing a multifunctional compound during the polymerization process not only requires the increase of the separation and recovery process of the multifunctional compound, but also has a certain impact on the processing performance of the product. CN107108893 achieves an increase in polymerization yield, particle size and particle strength by adding sodium hydroxide aqueous solution before the second stage polymerization, but the addition of sodium hydroxide aqueous solution will cause a large amount of N-methylpyrrolidone (NMP for short) to deteriorate, thereby increasing the content of impurities in the final PPS product. CN102105513 achieves an increase in the particle size of PPS particles and an improvement in polymerization yield by adding a NMP solution of p-dichlorobenzene during the cooling stage, but the inhibitory effect on the generation of ultrafine oligomer powder waste is limited, and the increase in p-DCB residue will reduce product quality. CN107636045 achieves an increase in the particle size and particle strength of PPS particles by adding a sodium acetate aqueous solution before the second stage polymerization, but does not effectively inhibit the generation of ultrafine oligomer powder waste.
[0006] In summary, it is necessary to develop a new preparation technology that can significantly reduce the amount of ultrafine powdery waste oligomers generated during the polymerization of polyphenylene sulfide. Summary of the invention
[0007] The problem to be solved by the present invention is to provide a polyphenylene sulfide resin and a preparation method thereof, focusing on reducing the by-product in the polymerization process of polyphenylene sulfide - ultrafine oligomer powder waste; and the polyphenylene sulfide resin has excellent yellowing resistance.
[0008] To solve the above problems, the inventors conducted systematic research work, focusing on reducing the byproducts of polyphenylene sulfide polymerization process - oligomer ultrafine powder waste. The polymerization reaction was carried out in an organic polar solvent using sulfur source, alkali metal hydroxide, and dihalogen aromatic compound as raw materials. When the conversion rate of dihalogen aromatic compound was greater than 50%, the material passing through the external circulation pipeline was in a turbulent state to enhance the mixing effect of the polymerization system, reduce the generation of oligomer ultrafine powder waste and improve the polymerization yield.
[0009] The technical solution adopted by the present invention is as follows:
[0010] The first aspect of the present invention provides a polyphenylene sulfide resin comprising a structure represented by formula (I),
[0011]
[0012] The polyphenylene sulfide resin has the following characteristics:
[0013] In a differential molecular weight distribution curve obtained by measurement based on gel permeation chromatography using polystyrene as a conversion standard, with the logarithmic value ln(M) of the molecular weight M as the horizontal axis and dw / dln(M) obtained by differentiating the concentration percentage w with the logarithmic value ln(M) of the molecular weight as the vertical axis, the ratio of the value obtained by integrating dw / dln(M) when 6.90≤ln(M)≤9.21 to the value obtained by integrating dw / dln(M) over the entire range of ln(M) is less than 5%, for example 4%, 3%, 2%, or 1%.
[0014] In some embodiments, the polyphenylene sulfide resin has a molecular weight distribution of less than 5.0.
[0015] In some embodiments, the polyphenylene sulfide resin has a yellowing index ΔYI of less than 0.3 after a 3 mm thick test piece is kept at 320° C. for 10 minutes.
[0016] Another aspect of the present invention provides a method for preparing the polyphenylene sulfide resin.
[0017] A method for preparing a polyphenylene sulfide resin, the method comprising the following steps:
[0018] (1) Dehydration stage: Over a certain period of time, the mixture of organic polar solvent, sulfur source, water and alkali metal hydroxide is gradually heated to remove water from the system.
[0019] (2) One-stage polymerization: After dehydration is completed, a mixture of a dihalogen aromatic compound and an organic polar solvent is added, and the temperature is raised to a certain temperature and pressure to generate a polymerization reaction mixture containing a prepolymer.
[0020] (3) Two-stage polymerization: When the conversion rate of the dihalogen aromatic compound is greater than 50%, the material in the external circulation pipeline is placed in a turbulent state to enhance the mixing effect of the polymerization system. The temperature is continued to rise to a certain temperature, and a phase separation agent is added to place the polymerization system in a phase separation state. The generated prepolymer is further reacted under a certain pressure.
[0021] (4) Post-treatment: The polymerization mixture is cooled, the reaction slurry is centrifuged, washed and filtered with acetone, then washed and filtered with an acid solution, and finally washed with hot water.
[0022] Specifically, the preparation method comprises:
[0023] (1) Dehydration stage: Over a certain period of time, the mixture of organic polar solvent, sulfur source, water and alkali metal hydroxide is gradually heated to remove water from the system.
[0024] In the method for preparing polyphenylene sulfide resin, the organic polar solvent in step (1) is selected from N-alkyl pyrrolidone compounds, N-cycloalkyl pyrrolidone compounds, N,N-dialkyl imidazolidinone compounds, tetraalkyl urea compounds, and hexaalkyl phosphoric acid triamide compounds;
[0025] Preferably, the N-alkylpyrrolidone compound or N-cycloalkylpyrrolidone compound is preferably N-methyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, etc.; the N,N-dialkylimidazolidinone compound is preferably 1,3-dialkyl-2-imidazolidinone, etc.; the tetraalkylurea compound is preferably tetramethylurea, etc.; the hexaalkylphosphoric acid triamide compound is preferably hexamethylphosphoric acid triamide, etc.;
[0026] The organic polar solvent is more preferably N-methyl-2-pyrrolidone.
[0027] The molar ratio of the organic polar solvent to the sulfur source in the dehydration stage is preferably 0.2-4.0, more preferably 0.5-3.
[0028] In the method for preparing polyphenylene sulfide resin, the sulfur source in step (1) is preferably lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, lithium hydrosulfide, sodium hydrosulfide, potassium hydrosulfide, rubidium hydrosulfide, cesium hydrosulfide, more preferably sodium sulfide or sodium hydrosulfide.
[0029] In the method for preparing polyphenylene sulfide resin, the alkali metal hydroxide in step (1) is preferably sodium hydroxide, calcium hydroxide, lithium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, more preferably sodium hydroxide, and the molar ratio of the amount of alkali metal hydroxide to the sulfur source in the dehydration stage is preferably 0 to 2, more preferably 0.5 to 1.5.
[0030] The molar ratio of water added in the dehydration stage to the sulfur source is preferably 0-20, more preferably 4-10.
[0031] In the method for preparing polyphenylene sulfide resin, in the dehydration stage described in step (1), the terminal temperature is preferably 120-260° C., more preferably 180-220° C., the heating rate is preferably 0.1-3.5° C. / min, more preferably 0.5-2.0° C. / min, the molar ratio of the residual water to the sulfur source at the end of the dehydration stage is preferably 0.5-3.0, more preferably 0.8-1.8, and the dehydration time of the dehydration stage is preferably 20-240 min, more preferably 60-180 min.
[0032] (2) One-stage polymerization: After dehydration is completed, a mixture of a dihalogen aromatic compound and an organic polar solvent is added, the temperature is raised to a certain temperature, and a polymerization reaction is carried out under a certain pressure to generate a reaction mixture containing a prepolymer.
[0033] In the method for preparing polyphenylene sulfide resin, the dihalogen aromatic compound in step (2) is preferably o-dichlorobenzene, m-dichlorobenzene, p-dichlorobenzene, dichlorotoluene, dichlorobiphenyl, dichlorobenzoic acid, dichlorodiphenyl ether, dichlorodiphenyl sulfone, dichlorodiphenyl sulfoxide, dichlorobenzophenone, etc., and p-dichlorobenzene is more preferred; the molar ratio of the dihalogen aromatic compound to the sulfur source is preferably 0.5 to 2.0, and more preferably 0.9 to 1.1.
[0034] In the method for preparing polyphenylene sulfide resin, the polymerization temperature in step (2) is preferably 180-260° C., preferably 200-240° C., the polymerization pressure is preferably 0-2 MPa, more preferably 0.2-0.8 MPa, the reaction time is preferably 30-240 min, more preferably 60-180 min; the conversion rate of the dihalogen aromatic compound is preferably 50%-98%, more preferably 60-95%.
[0035] The molar ratio of the total amount of the organic polar solvent to the sulfur source in the polymerization stage is preferably 1-6, more preferably 2-5.
[0036] (3) Two-stage polymerization: After the first-stage polymerization is completed, the material passing through the external circulation pipeline is placed in a turbulent state to enhance the mixing effect of the polymerization system. The temperature is continued to rise to a certain temperature, and a phase separation agent is added to place the polymerization system in a phase separation state. The generated prepolymer is further reacted under a certain pressure.
[0037] In the method for preparing polyphenylene sulfide resin, the Reynolds number Re of the material in the external circulation pipeline in step (3) is preferably 4000 to 40000, and more preferably 10000 to 30000.
[0038] In the method for preparing polyphenylene sulfide resin, the polymerization temperature in step (3) is 240-290° C., preferably 250-270° C., the polymerization pressure is 0-3 MPa, preferably 1-1.8 MPa, the reaction time is preferably 30-240 min, more preferably 60-180 min; the conversion rate of the dihalogen aromatic compound is preferably 80%-100%, more preferably 90-99.5%.
[0039] In the method for preparing polyphenylene sulfide resin, the phase separation agent in step (3) is preferably water, organic carboxylic acid metal salts, organic sulfonic acid metal salts, alkali metal halides such as lithium halides, alkaline earth metal halides, alkaline earth metal salts of aromatic carboxylic acids, alkali metal phosphates, alcohols, paraffin hydrocarbons and other compounds; the organic carboxylic acid metal salts are preferably alkali metal carboxylates such as lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, lithium benzoate, sodium benzoate, sodium phenylacetate, potassium p-methylbenzoate and the like; the molar ratio of the phase separation agent to the initial sulfur source is preferably 0 to 5, more preferably 1 to 2.
[0040] (4) Post-treatment: The polymerization mixture is cooled, the reaction slurry is centrifuged, washed with acetone, filtered, then washed with an acid solution, filtered, and finally washed with hot water.
[0041] In the method for preparing polyphenylene sulfide resin, the acid in step (4) is preferably hydrochloric acid, sulfuric acid, nitric acid, carbonic acid, acetic acid, oxalic acid, malic acid, citric acid, more preferably hydrochloric acid or acetic acid.
[0042] The effects of the present invention are:
[0043] The polyphenylene sulfide resin of the present invention has a value obtained by integrating dw / dln(M) when 6.90≤ln(M)≤9.21, a ratio of a value obtained by integrating dw / dln(M) over the entire range of ln(M) of less than 5%, a low amount of oligomer ultrafine powder waste generated, and excellent yellowing resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a reaction flow diagram in the embodiment. DETAILED DESCRIPTION
[0045] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0046] The analysis and evaluation methods involved in the embodiments or comparative examples are as follows:
[0047] (1) Weight average molecular weight
[0048] The weight average molecular weight (Mw) of the polymer was measured using a high temperature gel permeation chromatograph (GPC) PL-GPC220 model, equipped with an Agilent 1000 series pump, a high temperature autosampler, a dissolution device PL.SP260 model, a gel chromatography column: 2μm×10μm, MIXED-B, 300mm×7.5mm, and a differential refractometer under the following conditions. The weight average molecular weight was calculated as a polystyrene conversion value;
[0049] Solvent: 1-Chloronaphthalene
[0050] Test temperature: 210℃
[0051] Detector: UV detector (360nm)
[0052] Sample injection volume: 200 μl (concentration: 0.05 mass %)
[0053] Mobile phase flow rate: 110ml / min
[0054] Standard polystyrene: 5 kinds of standard polystyrene of 616000, 113000, 26000, 8200 and 600.
[0055] Using the calibration curve obtained with standard polystyrene, the elution time of the time curve of the intensity distribution detected in the differential refractometer (RI) of the GPC device (generally referred to as the elution curve) is converted into molecular weight. Here, since the RI detection intensity is proportional to the component concentration, the intensity area is calculated when the total area of the elution curve is set to 100%, and the concentration fraction of each elution time is calculated. The concentration fractions are accumulated in sequence, and the logarithmic value of the molecular weight (ln(M)) is plotted on the horizontal axis, and the cumulative value of the concentration fraction (w) is plotted on the vertical axis, thereby obtaining an integrated molecular weight distribution curve;
[0056] Next, the slope of the curve at each molecular weight logarithm is calculated, i.e., the differential value of the integrated molecular weight distribution curve. The differential molecular weight distribution curve is plotted with the logarithm of the molecular weight (ln(M)) as the horizontal axis and the above differential value (dw / dln(M)) as the vertical axis. Therefore, the differential molecular weight distribution refers to the value obtained by differentiating the concentration fraction (w) by the logarithm of the molecular weight (ln(M)), i.e., "dw / dln(M)". Through this differential molecular weight distribution curve, we can directly read the differential molecular weight distribution dw / dln(M) at a specific ln(M) value.
[0057] (2) Polymerization yield
[0058] Assuming that all the sodium hydrosulfide added to the reactor is converted into PPS, the mass of PPS at this time (theoretical amount) is set as a reference value, and the ratio of the mass of PPS actually recovered (the oversize material collected by an 80-mesh sieve) to the reference value is calculated and defined as the polymerization yield (unit: wt.%).
[0059] (3) Yield of ultrafine powdery waste of oligomers
[0060] Assuming that all the sodium hydrosulfide put into the reactor is converted into PPS, the mass of PPS at this time (theoretical amount) is set as the reference value, and the ratio of the mass of the undersize collected by the 300-mesh sieve to the reference value is calculated, which is defined as the yield of ultrafine powdery waste of oligomers (unit: wt.%).
[0061] (4) Conversion rate of p-dichlorobenzene
[0062] The amount of p-dichlorobenzene remaining in the slurry after the polymerization was completed was determined by gas chromatography, and the conversion rate of p-dichlorobenzene was calculated based on the remaining amount, the amount of p-dichlorobenzene fed, and the amount of sodium hydrosulfide fed.
[0063] (5) Reynolds number
[0064]
[0065] Where:
[0066] ρ---Density of the material during polymerization, measured by an online density meter, Kg / m 3 ;
[0067] u---Material flow rate in the external circulation pipeline, m / s;
[0068] d---diameter of the external circulation pipeline, m;
[0069] μ---Viscosity of the material during polymerization, obtained by online viscometer, Pa·s.
[0070] (6) △YI
[0071] The YI value of the test piece of polyphenylene sulfide resin is obtained by testing with a colorimeter UltraScan PRO. First, the powder is injection-molded into a 3mm thick test piece at 320°C using a Haitian MA900II 1260 injection molding machine, and then the test piece YI is obtained by testing. The powder stays in the screw of the injection molding machine for 10 minutes and is injection-molded into a 3mm thick test piece. The difference between the YI value of this test piece and the YI value during direct injection molding is △YI.
[0072] Example
[0073] The following examples are given to further explain the embodiments of the present invention. Of course, the present invention is not limited to the following examples.
[0074] Example 1
[0075] 1. Dehydration stage:
[0076] In a 50L titanium reactor, 46% NaSH aqueous solution (6855.16g, 56.25mol), 50% NaOH aqueous solution (4275g, 53.44mol), and NMP (9466g, 95.63mol) were added, and the molar ratio of NaOH / NaSH was 0.95. The temperature was raised to 180°C at a speed of 100rpm and a heating rate of 1.2°C / min. 5248.9g of aqueous solution (water content 88.1%) was removed. At this time, the remaining water content in the system was H 2 The molar ratio of O / NaSH was 1.2, and the dehydration was completed, and the material temperature was reduced to 150°C.
[0077] 2. One-stage aggregation:
[0078] p-DCB (8434.86 g, 57.38 mol) and NMP (9466 g, 95.63 mol) were pumped into the reactor, and the molar ratio of p-DCB / NaSH was 1.02. The stirring speed of the reactor was increased to 200 rpm, and the temperature was raised to 230° C. in 90 min. The first stage polymerization was completed at 230° C. for 2.5 hours. After the first stage polymerization, the conversion rate of p-DCB was 88%, and the terminal pressure was 0.53 MPa.
[0079] 3. Two-stage aggregation
[0080] After the first stage polymerization, the external circulation pump of the reactor was started, and the lift of the external circulation pump was adjusted so that the Reynolds number of the material in the external circulation pipeline was 15000. The temperature was then raised to 260°C at a heating rate of 2.0°C / min, and water (1518.75g, 84.38mol) was pumped into the reactor through a pump. The reaction was continued for 2 hours to complete the second stage polymerization. After the second stage polymerization, the conversion rate of p-DCB was 99.3%, and the terminal pressure was 1.67MPa.
[0081] 4. Post-processing stage
[0082] After the polymerization, the external circulation pump of the reaction liquid was turned off, and the material temperature was reduced to 120°C in 1 hour. The product was sieved with a 80-mesh screen, and the material on the screen was centrifuged and filtered. The filter cake was washed and filtered with acetone, and then washed and filtered with a hydrochloric acid solution, and washed with boiling water for 4 times. The obtained granular PPS was dried at 120°C for 8 hours.
[0083] The undersize of the 80-mesh sieve was collected and then screened using a 300-mesh sieve. The undersize of the 300-mesh sieve was collected and washed with boiling water 5 times. The collected fine powder was dried at 80° C. for 12 hours to obtain ultrafine powder waste of oligomers.
[0084] Embodiment 2-4
[0085] The preparation method of each embodiment is consistent with the above steps, except that the Reynolds number Re of the material in the external circulation pipe is changed only by adjusting the head of the external circulation pump. The Reynolds numbers Re of the material in the external circulation pipe of Examples 2-4 are 10000, 20000 and 30000 respectively.
[0086] Comparative Example
[0087] Comparative Example 1
[0088] The preparation method of Comparative Example 1 is consistent with the preparation method of Example 1, except that the external circulation pump of the pipeline is not started in the second-stage polymerization, and the materials in the polymerization system are mixed only by stirring in the reactor.
[0089] Comparative Examples 2-3
[0090] The preparation method of Comparative Example 2-3 is consistent with the preparation method of Example 1, except that the Reynolds number Re of the material in the external circulation pipe is changed only by adjusting the head of the external circulation pump. The Reynolds numbers Re of the material in the external circulation pipe of Comparative Examples 2-3 are 1000 and 3000, respectively.
[0091] Comparative Example 4
[0092] The preparation method of comparative example 4 is consistent with that of example 1, except that only the start time of the external circulation pump of the reactor is changed. In comparative example 4, the external circulation pump of the reaction liquid is started before the start of the first-stage polymerization, and the head of the external circulation pump is adjusted so that the Reynolds number of the material in the external circulation pipeline is 15,000.
[0093] The test data of each embodiment and comparative example are shown in Table 1.
[0094] Table 1 Test data of embodiments and comparative examples
[0095]
[0096]
[0097] From the above data comparison, it can be seen that by making the materials passing through the external circulation pipeline in a highly turbulent state (Re≥10000) before the second stage polymerization to enhance the mixing effect of the polymerization system, the generation of ultrafine powdery waste of oligomers can be reduced to less than 5%. The polyphenylene sulfide resin prepared by the present invention has excellent yellowing resistance.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A polyphenylene sulfide resin, characterized in that: Containing the structure shown in formula (I): The polyphenylene sulfide resin has the following characteristics: in a differential molecular weight distribution curve obtained by measurement based on gel permeation chromatography with polystyrene as the conversion standard, with the logarithmic value ln(M) of the molecular weight M as the horizontal axis and dw / dln(M) obtained by differentiating the concentration percentage w with the logarithmic value ln(M) of the molecular weight as the vertical axis, a ratio of a value obtained by integrating dw / dln(M) when 6.90≤ln(M)≤9.21 to a value obtained by integrating dw / dln(M) over the entire range of ln(M) is less than 5%.
2. The polyphenylene sulfide resin according to claim 1, characterized in that: The molecular weight distribution of the polyphenylene sulfide resin is less than 5.
0.
3. The polyphenylene sulfide resin according to claim 1, characterized in that: The yellowing index ΔYI of a 3 mm thick test piece of the polyphenylene sulfide resin after being kept at 320° C. for 10 minutes is less than 0.
3.
4. A method for preparing a polyphenylene sulfide resin, characterized in that: The preparation method comprises the following steps: (1) Dehydration stage: The mixture of organic polar solvent, sulfur source, water and alkali metal hydroxide is gradually heated to remove water from the system; (2) One-stage polymerization: After dehydration is completed, a dihalogen aromatic compound and an organic polar solvent are added, the temperature is raised, and a polymerization reaction is carried out to generate a reaction mixture containing a prepolymer; (3) Second stage polymerization: After the first stage polymerization is completed, the material passing through the external circulation pipeline is placed in a turbulent state, and the temperature is continued to rise to a certain temperature, and a phase separation agent is added to allow the generated prepolymer to further react; (4) Post-treatment: The polymerization mixture is cooled, and the reaction slurry is centrifuged, washed, and filtered.
5. The preparation method according to claim 4, characterized in that: In step (1), the organic polar solvent is selected from N-alkylpyrrolidone compounds, N-cycloalkylpyrrolidone compounds, N,N-dialkylimidazolidinone compounds, tetraalkylurea compounds, and hexaalkylphosphoric acid triamide compounds; Preferably, the N-alkyl pyrrolidone compound or the N-cycloalkyl pyrrolidone compound is preferably N-methyl-2-pyrrolidone or N-cyclohexyl-2-pyrrolidone; the N,N-dialkyl imidazolidinone compound is preferably 1,3-dialkyl-2-imidazolidinone; the tetraalkyl urea compound is preferably tetramethyl urea; the hexaalkyl phosphoric acid triamide compound is preferably hexamethyl phosphoric acid triamide; The molar ratio of the organic polar solvent to the sulfur source in the dehydration stage is preferably 0.2 to 4.0, more preferably 0.5 to 3; The sulfur source is selected from lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, lithium hydrosulfide, sodium hydrosulfide, potassium hydrosulfide, rubidium hydrosulfide, and cesium hydrosulfide; The alkali metal hydroxide is selected from sodium hydroxide, calcium hydroxide, lithium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide; the molar ratio of the alkali metal hydroxide to the sulfur source is preferably 0 to 2, more preferably 0.5 to 1.5; The molar ratio of water added in the dehydration stage to the sulfur source is preferably 0-20, more preferably 4-10.
6. The preparation method according to claim 4 or 5, characterized in that: In step (1), in the dehydration stage, the terminal temperature is 120-260° C., more preferably 180-220° C., the heating rate is 0.1-3.5° C. / min, more preferably 0.5-2.0° C. / min, and the molar ratio of the residual water to the sulfur source at the end of the dehydration stage is 0.5-3.0, more preferably 0.8-1.
8.
7. The preparation method according to claim 4 or 5, characterized in that: In step (2), the dihalogen aromatic compound is selected from o-dichlorobenzene, m-dichlorobenzene, p-dichlorobenzene, dichlorotoluene, dichlorobiphenyl, dichlorobenzoic acid, dichlorodiphenyl ether, dichlorodiphenyl sulfone, dichlorodiphenyl sulfoxide, dichlorobenzophenone, and more preferably p-dichlorobenzene; Preferably, the molar ratio of the dihalogen aromatic compound to the sulfur source is 0.5 to 2.0, more preferably 0.9 to 1.1; The polymerization temperature of step (2) is preferably 180-260° C., preferably 200-240° C., the polymerization pressure is preferably 0-2 MPa, more preferably 0.2-0.8 MPa, the reaction time is preferably 30-240 min, more preferably 60-180 min; the conversion rate of the dihalogen aromatic compound is preferably 50%-98%, more preferably 60-95%; The molar ratio of the total amount of the organic polar solvent to the sulfur source in the polymerization stage is preferably 1-6, more preferably 2-5.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (3), the Reynolds number Re of the material in the external circulation pipeline is 4000 to 40000, more preferably 10000 to 30000; The polymerization temperature of step (3) is 240-290° C., preferably 250-270° C., the polymerization pressure is 0-3 MPa, preferably 1-1.8 MPa, the reaction time is 30-240 min, more preferably 60-180 min; the conversion rate of the dihalogen aromatic compound reaches 80%-100%, more preferably 90-99.5%.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The phase separation agent in step (3) is selected from water, organic carboxylic acid metal salts (preferably lithium acetate, sodium acetate, potassium acetate, sodium propionate, lithium valerate, lithium benzoate, sodium benzoate, sodium phenylacetate, potassium p-toluate), organic sulfonic acid metal salts, alkali metal halides such as lithium halides, alkaline earth metal halides, alkaline earth metal salts of aromatic carboxylic acids, alkali metal phosphates, alcohols and paraffin hydrocarbons; the molar ratio of the phase separation agent to the sulfur source is preferably 0 to 5, more preferably 1 to 2.
10. The preparation method according to any one of claims 4 to 9, characterized in that: Step (4) comprises: cooling the mixture obtained by polymerization, centrifuging the reaction slurry, washing with acetone, filtering, washing with an acid solution, filtering, and finally washing with hot water; The acid is preferably hydrochloric acid, sulfuric acid, nitric acid, carbonic acid, acetic acid, oxalic acid, malic acid, citric acid, more preferably hydrochloric acid or acetic acid.
Citation Information
Patent Citations
Production of polyarylene sulfide
JP1988039926A
Preparation of omelet like hand-made one
JP1989043169A
Method for recovering polyphenylene sulfide oligomer
JP2007106784A
Surface roughening of resin molded articles for metallizing
US5342654A
Cited By
Method for determining real molecular weight of PPS resin by using gel chromatograph
CN121027366A
A method for determining the true molecular weight of a PPS resin using a gel permeation chromatograph
CN121027366B
Preparation method of polyphenylene sulfide resin
CN121293498A
A method for producing a polyphenylene sulfide resin
CN121293498B